When practices count: Implementation of sustainable consumption and production in automotive supply chains. Issue 5 (30th September 2019) - Uniyal, Surbhi; Mangla, Sachin Kumar; Patil, Pravin
Abstract : Purpose: Sustainable consumption and production (SCP) assist managers to improve their operational efficiency while aiming at reducing the generation of waste. The purpose of this paper is to construct a structural model of the SCP practices in a supply chain context. Design/methodology/approach: The work is based on the experience of supply chain professionals, a case study and literature review related to SCP. The present work recommends an assessment framework by prioritizing the SCP oriented practices using best-worst method. Findings: The current work is an effort to understand the significance of SCP practices and to reveal their level of influence in developing a sustainable culture in value chains. Data for this work are derived from an automotive company operating in India. Findings reveal that the "resource efficiency" acquires the highest rank and "sharing assets" acquires the last lank among all SCP practices. Research limitations/implications: It is difficult to finalize the SCP practices. This work uses the expert's approach for this. In this way, the process needs to be conducted very carefully. Practical implications: This research can assist automotive managers and practitioners in efficiently utilizing their companies' resources, which would result in superior business effectiveness by generating higher employment opportunities in value chains. Originality/value: Efforts have been made to contribute in the identification and analysis of SCP oriented practices. The developed structural model will help in understanding the ranking of practices.